Structural peculiarities of paremias with predicates state in the Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article studies the structural peculiarities of paremias with verbal and adverbial predicates state in the Ukrainian language, revealing the basic principles upon which delimitation based of proverbs and sayings on designs simple and complex syntactic structures.
Keywords: paremias; predicate; state; opinions; comparisons; parallelism; contrast